Evaluasi Kriteria Kerusakan tanah untuk Produksi Biomassa pada Lahan Kering di Kabupaten Subang - Budy Frasetya Taufiq Qurrahman; Abraham Suriadikusumah; Rachmat Haryanto (Soilrens, 2016)
Government  Regulation No.  150  Year  2000  on  Soil  Degradation Control  for Production of Biomass  is  a  testament  to  the seriousness  of  the government  in anticipating  and  addressing land degradation due  to  biomass  production.  In fact,  unsustainable intensification can cause soil degradation. Soil  degradation parameters  may  change in accordance  with  the  conditions  of  the district/city. This study aimed to evaluate the standard criteria of soils degradation on dry land in Subang District. Did having high accuracy and whether the ten parameters are decisive parameters. The research  method used  was  a  descriptive survey.  Data  from  the field and then  analyzed  using discriminant analysis. The results of discriminant analysis for soil degradation standard criteria in Subang District, determining parameters were selected 4 parameters, ie bulk density, sand fraction,electrical conductivity, soil reaction (pH) with the level of accuracy obtained discriminant function 74,1 % with corelation coeficient 0,866 or 86,6 % and determination coeficient (R2) 0,75 or 75 %. Keywords: Accuracy Discriminant Function, Evaluation Standards Criteria, Parameters Determinant